2018
DOI: 10.1214/17-aap1322
|View full text |Cite
|
Sign up to set email alerts
|

Beating the omega clock: An optimal stopping problem with random time-horizon under spectrally negative Lévy models

Abstract: We study the optimal stopping of an American call option in a random time-horizon under exponential spectrally negative Lévy models. The random time-horizon is modeled as the so-called Omega default clock in insurance, which is the first time when the occupation time of the underlying Lévy process below a level y, exceeds an independent exponential random variable with mean 1/q > 0. We show that the shape of the value function varies qualitatively with different values of q and y. In particular, we show that f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(50 citation statements)
references
References 24 publications
1
49
0
Order By: Relevance
“…With anxiety, that is, q>0, we consider the function g(·) given by truerightg(x)=efalse(1ρfalse)x()11ρ1Λ(x)1emwith1emnormalΛ(x):=dnormaldxlogIfalse(r,qfalse)(x),where scriptI(r,q)false(·false) is defined by scriptI(r,q)false(xfalse):=0normaleΦ(r+q)uW(r)false(u+xfalse)du,xR.The function g(·) is continuous everywhere with one possible discontinuity at 0. It is known from Rodosthenous and Zhang (2018, Lemma 4.2) that Λ(·) is strictly decreasing over R+, with limits Λ(0+)Φ(r+q) and Λ()=Φ(r…”
Section: Model and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With anxiety, that is, q>0, we consider the function g(·) given by truerightg(x)=efalse(1ρfalse)x()11ρ1Λ(x)1emwith1emnormalΛ(x):=dnormaldxlogIfalse(r,qfalse)(x),where scriptI(r,q)false(·false) is defined by scriptI(r,q)false(xfalse):=0normaleΦ(r+q)uW(r)false(u+xfalse)du,xR.The function g(·) is continuous everywhere with one possible discontinuity at 0. It is known from Rodosthenous and Zhang (2018, Lemma 4.2) that Λ(·) is strictly decreasing over R+, with limits Λ(0+)Φ(r+q) and Λ()=Φ(r…”
Section: Model and Main Resultsmentioning
confidence: 99%
“…Part of our analysis builds on the results obtained in Theorems 4.2 and 4.3 for the problem (5), which generalizes Rodosthenous and Zhang (2018, Theorems 2.4 and 2.5) to the class of CRRA utility functions. To be more precise, we show that the original optimal stopping problem (2) reduces to its simplified version (5) for specific ranges of parameter values and certain levels of asset price best performance.…”
Section: Introductionmentioning
confidence: 98%
“…Optimal stopping problems with a random discounting find their applications in many areas such as finance and applied probability (for instance, in problems driven by continuously time-changed Markov processes [4], or problems with random maturity [20]). Perpetual optimal stopping of time-homogeneous diffusions with a random discounting rate were studied in Dayanik [5], by exploiting Dynkin's concave characterizations of the excessive functions.…”
Section: Introductionmentioning
confidence: 99%
“…While this is a very promising approach within diffusion framework, it shows limitations when jumps present. For example, for perpetual American call options on exponential Lévy models under an occupation time type discounting [20], it is shown that there can be two disjoint components for both the continuation and the stopping regions, which appear alternately. Possible overshoots thus make it difficult to apply [5]'s approach directly.…”
Section: Introductionmentioning
confidence: 99%
“…It turned out that the resulting value functions and optimal stopping boundaries in models with exponentially distributed time horizons independent of the underlying processes are analytically more tractable than those obtained in models with fixed time horizons. Other optimal stopping problems for exponentially distributed time horizons which are dependent of the underlying Lévy process were recently considered in Rodosthenous and Zhang (2018). Glattfelder et al (2011) suggested a new paradigm, the directional changes, that summarises the price dynamics in the financial market.…”
mentioning
confidence: 99%